Preparedness against bioterrorism and re-emerging infectious diseases - Kocik, Janusz; Janiak, Marek; Negut, Marian (NATO science series. Life and behavioural sciences, 2004)
In these papers drawn from the January 2003 workshop, contributors describe methods of building integrated systems to combat epidemics and bio-terrorism. Their general topics include developing epidemiology with laboratory support as a biological attack identification tool, using national approaches to biodefense, and conducting risk assessment, cr.